(3GdeSFhdjI GdLfGFjI Yf GdLQjeI GdGFJeGfjI (B/ s - (3eMeO HgLJ CMeO eMeOs; (3YeQ eMeO SGde s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2021)
(3dbO TgOJ HdGO GdYGde (B- (3h ef Hjfge eUQ (B- (3JWhQGJ gGFdI ai cGaI efGMi GdMjGI GdeNJdaI ShGA ef GdfGMjI GdSjGSjI(B: (3Ch GdGbJUGOjI(B: (3Ch GdGLJeGYjI(B. (3h cGf Pdc fJjLI GdJCKQ GdTOjO HeG TgOg GdYGde ai GdBhfI GdCNjQI ef XghQ GdJcfhdhLjG GdMOjKI(B: (3h JWhQgG ai eLGd GdGJUGd h GdEfJQfJ GdJi LYdJ GdYGde eLQO bQjI UZjQI(B. (3aefP HOGjI GdNdb (B- (3h LYd Gddg EOe NdjaI aj GdCQV (B- (3h GdMjGI GdHTQjI ai JWhQ OGFe h eSJeQ(B: (3ade Jcf GdMjGI GdHTQjI Ydi GdfMh GdeJYGQa Ydjg GdBf Hd cGfJ aj bOje GdCRd h efP YbhO WhjdI (B- (3GdMjGI GdHTQjI (B- (3JeJGR HGdHOGFjI(B. (3abO YGT GdEfSGf GdHOGFi hMjOG ai HOGjI GdCeQ eY GdJWhQ XgQJ GdLeGYGJ h GdJi JYGbHJ YdjgG JWhQGJ cKjQI Edi Cf XgQJ acQI GdOhdI(B: (3h de Jcf GdOhdI Ydi GdfMh GdeJYGQa Ydjg MGdjG(B. (3Hd cGfJ ai HOGjI GdCeQ cd LeGYI jMcegG aQO hGMO jbhe Ydi MeGjJgG ef GdgLeGJ GdNGQLjI(B: (3h GdMaGX Ydi GdJYGedGJ Hjf CaQGO Jdc GdLeGYI(B. (3Ke CNPJ GdOhdI JJWhQ TjFkG aTjFkG(B: (3hjJSY eLGdgG Edi Cf CUHMJ GdOhdI PGJ fXGe SjGSi eJcGed(B: (3h dgG eaghe bGfhfi NGU HgG(B: (3h SdWI JYed Ydi EOGQI TFhf GdHdGO ai cGaI efGMi GdMjGI ShGA GdSjGSjI(B: (3Ch GdGbJUGOjI(B: (3ChGdGLJeGYjI(B. (3h eY gPG GdJWhQ GdJi JYQVJ dg GdMjGI GdHTQjI JWhQJ cGaI efGMi GdMjGI(B: (3h dGSjeG GdeLGd GdGbJUGOi abO cGf GdGbJUGO ai HOGjI GdCeQ ai fXQ GdEfSGf eGgh EdG GdHMK Yf GdeCcd(B: (3h GdedHS(B: (3h GdeScf abO cGf gPG GdfTGW gh CbOe GdCfTWI GdGbJUGOjI GdJi YQagG GdEfSGf ai GdJGQjNs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2021s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B296-326s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdLQjeI GdGFJeGfjIs; (3GdWdHs; (3GdeSFhdjI GdLfGFjIs; (3GdGFJeGf GdeUQajs; (3CehGd GdHfhcs; (3EKHGJ GdLQjeI GdGFJeGfjIs; (3GdJUGdM Yf GdLQjeI GdGFJeGfjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs